The LOTTE system of tax microsimulation models - Zhiyang Jia; Bodil M. Larsen; Bård Lian; Runa Nesbakken; Odd E. Nygård; Thor Olav Thoresen; Trine Engh Vattø (Statistics Norway, Research Department, 2023)
Microsimulation models of the LOTTE system are key tools for tax policy-making in Norway and are extensively used in the budget process. The aim of this paper is to give an overview of the different modules in the LOTTE family - a non-behavioral tax-benefit model for personal income tax (LOTTESkatt), a labor supply model (LOTTE-Arbeid), and a model for distributional effects of commodity taxation (LOTTE-Konsum). In addition to providing descriptions of the designs of the three microsimulation models, we give examples of how the models are used in practical and academic work.
Keywords: C63; H24; H31; 330; microsimulation; tax-benefit model; labor supply; commodity taxation